The Tardenoisian concept in Polish Mesolithic studies - Płonka, Tomasz (Sprawozdania Archeologiczne, 2022)
The evolution of the concept of the Tardenoisian in Polish Mesolithic studies visibly falls into three phases, dating approximately to 1900-1970, 1971-1990, 1991-2016. In the first half of the twentieth century the geographical range of the Tardenoisian, known originally from French sites, was extended to areas in Central Europe, Poland included. Although criticised by Polish researchers of the Mesolithic already in the 1960s, this concept continued to appear in the literature until 1970. In the 1960s, 1970s and 1980s the local cultural taxonomy of the Polish Mesolithic was developed, based on meticulous analyses of the archaeological record. Using these sources, some researchers have recognized influences in southwestern Poland of the Western complex of Mesolithic cultures which includes e.g., the Tardenoisian and Beuronian. New material discovered after 1990 confirmed the presence of Beuronian sites in the Polish zone of the Sudeten. The upland and mountainous zone of Central Europe with its great diversity of lithic resources was heavily exploited by communities of this cultural tradition.